2014
DOI: 10.1007/s11356-014-3975-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 241Pu occurrence, distribution, and bioaccumulation in seabirds from northern Eurasia

Abstract: The paper presents unique data of plutonium 241Pu study in seabirds from northern Eurasia, permanently or temporally living at the southern Baltic Sea coast. Together, ten marine birds species were examined, as follows: three species that permanently reside at the southern Baltic, four species of wintering birds, and three species of migrating birds; 366 samples were analyzed. The obtained results indicated plutonium was non-uniformly distributed in organs and tissues of analyzed seabirds. The highest 241Pu co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Seabirds are typical double habitat (land and water) organisms, characterized by high body temperature and fast metabolism. Studies on 239+240 Pu concentration in southern Baltic sea seabirds showed that plutonium content was significantly differentiated among species, their tissues and organs [47,48]. The results of plutonium determination in marine organisms indicate its increase in the sequence as follows: seabirds < fish < zooplankton < phytoplankton < zoobenthos < phytobenthos.…”
Section: Plutonium 238 Pu 239 Pu 240 Pu and 241 Pumentioning
confidence: 99%
“…Seabirds are typical double habitat (land and water) organisms, characterized by high body temperature and fast metabolism. Studies on 239+240 Pu concentration in southern Baltic sea seabirds showed that plutonium content was significantly differentiated among species, their tissues and organs [47,48]. The results of plutonium determination in marine organisms indicate its increase in the sequence as follows: seabirds < fish < zooplankton < phytoplankton < zoobenthos < phytobenthos.…”
Section: Plutonium 238 Pu 239 Pu 240 Pu and 241 Pumentioning
confidence: 99%